Vancouver Through the Eyes of a Hobo: Experience, Identity, and Value in the Writing of Canada’s Depression-Era Tramps - McCallum, Todd (Labour/Le Travailleur, 2007)
Abstract As a window into contemporary debates about the concept of experience, this essay examines 1934’s Vancouver Through the Eyes of a Hobo, which may have the distinction of being the only extant book about hoboing in Depression-era Canada written by a self-identified transient, Victor Wadham Forster. Forster mapped for his readers a dialectic: Nature — an antimodern pastoral refuge where hoboes lived in freedom — stood against the City — a wholly modern capitalist nightmare, home to economic exploitation and its attendant moral degradations. Yet, the author also articulated his desire to destroy this way of life — and the foundation of his claims to authority as a writer — in order to effect his and every hobo’s reintegration with society. Casting off his avowed allegiance to tramping, Forster divined for his readers a third social formation, a new kind of capitalism infused with a Christian ethos of brotherhood and cooperation, and propped up by an unbounded white supremacy and a rigidly patriarchal division of labour. Herein lies the tragedy of Vancouver Through the Eyes of a Hobo: to save the hobo required the destruction of the hobo way of life.